Loch Shurrey (Scottish Historical and Archaeological Internet Reports, 2003)
This section described the appearance of the site prior to excavation and the methods employed for investigation. The wall comprised random rubble and soil resting on a thin foundation of flat slabs and rough cobbling. The entrance and part of the passageway survived. The interior was disturbed but sufficient flagstones remained in position to support the interpretation that the floor was originally composed of paving bedded on a layer of rough cobbling set into the natural clay subsoil. Charcoal from a hearth was radiocarbon dated. A post-socket contained a saddle quern and a reused cup marked stone was found within the wall tumble.